2023
DOI: 10.2147/opth.s390955
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure and Medication Changes Associated with Xen Gel Stent: A Systematic Review of the Literature

Abstract: The Xen gel stent (Allergan Inc, an AbbVie company; Dublin, Ireland) was conceived as an option for patients requiring modest IOP reduction but for whom trabeculectomy was not yet indicated. As with any glaucoma surgery, establishing criteria for patient selection and identifying factors that contribute to a high likelihood of success are important. To help guide clinical decisionmaking, a systematic review of published studies on the gel stent was performed, with the goal of understanding postoperative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Similarly, Yang et al [ 103 ], in a systematic review and metanalysis, did not find significant differences between XEN and phaco-XEN surgery in terms of IOP after surgery (standardized mean difference: −0.01, 95% CI −0.09 to 0.08, p value 0.894). Nevertheless, the reduction in the number of ocular hypotensive medications was greater in the XEN solo group ( p = 0.019) [ 102 ].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Yang et al [ 103 ], in a systematic review and metanalysis, did not find significant differences between XEN and phaco-XEN surgery in terms of IOP after surgery (standardized mean difference: −0.01, 95% CI −0.09 to 0.08, p value 0.894). Nevertheless, the reduction in the number of ocular hypotensive medications was greater in the XEN solo group ( p = 0.019) [ 102 ].…”
Section: Resultsmentioning
confidence: 82%
“…Similarly, Yang et al [ 102 ] did not find significant differences in IOP lowering between XEN-solo and XEN + Phaco (standardized mean difference: −0.01, 95% CI −0.09 to 0.08, p value 0.894). Moreover, Panarelli et al [ 103 ] reported that, on average, successful gel stent surgery achieved a postoperative IOP of approximately 14.0 mm Hg and reduction to fewer than 1 ocular hypotensive medication.…”
Section: Resultsmentioning
confidence: 99%
“…Apesar do número reduzido de olhos e, também, pelo fato de esta série ter sido constituída pelos primeiros olhos submetidos ao procedimento pelo cirurgião, o resultado encontrado é bastante similar ao encontrado por análise conjunta de um grupo de estudos, realizado por Panarelli et em metanálise recente. (9) Eles encontraram uma redução média absoluta da PIO de 6,6 mmHg para o mesmo tempo de acompanhamento pós-operatório. (9) Isso demonstra que, mesmo no início da curva de aprendizado, é possível alcançar resultados semelhantes ao encontrados na literatura.…”
Section: Discussionunclassified
“…A técnica cirúrgica usa habitualmente uma abordagem ab interna, sem a necessidade de abertura conjuntival e nem de suturas. (8,9) Esse implante já é de uso corrente nos principais países da Europa, da Ásia e da América do Norte há aproximadamente uma década, contudo, só foi disponibilizado para o mercado brasileiro no começo de 2023.…”
Section: Introductionunclassified
See 1 more Smart Citation